ANALISIS IBDAL DALAM AL-QUR’AN PERSPEKTIF ABU HAYYAN AL-ANDALUSIA AN-NAYSABURI DAN AN-NASAFI (Studi Komparasi Atas Penafsiran Q.S. At-Taubah: 33, Q.S. Al-Fath: 28, Dan Q.S. As-Saf: 9) - ‘Amilatu Sholihah; Moh. Abdul Kholiq Hasan (Universitas Muhammadiyah Surakarta, 2020)
This study discusses about the substitutions (ibdal) contained in the Qur’an, especially in Q.S at-Taubah (9): 33, Q.S al-Fath (48): 28, and Q.S as-Saf (61): 9 which discusses the message of the Prophet. Ibdal is similiar editions verses in action but have little difference in letters, words or sentences. There are three interpreting works that will be used as objects in this study, namely the interpretation of the work of Abu Hayyan, an-Naysaburi and an-Nasafi. Based on ibdal above, there are several questions related to the application of ibdal on the interpretation of the three verses above, namely: 1. How is ibdal in the Qur'an? 2. How is the interpretation of Abu Hayyan al-Andalusia, an-Naysaburi, and an-Nasafi to ibdal Q.S at-Taubah (9): 33, Q.S al-Fath (48): 28, and Q.S as-Saf (61): 9 and what is the function of ibdal in these verses? This research is a type of library research, using a qualitative approach that is descriptive-analytical, namely by describing the history of ibdal in the Qur'an, ibdal, ibdal types and examples. Explain the interpretation of Abu Hayyan al-Andalusia, an-Naysaburi, and an-Nasafi to ibdal on QS at-Taubah (9): 33, Q.S al-Fath (48): 28, and Q.S as-Saf (61): 9. The results of this study indicate: 1. Ibdal in the Qur'an is the verses of the Qur'an which have similarities and have little difference in terms of letters, words or sentences. There are at least three types, namely: ibdal of single and plural pronoun, ibdal ثم with ف, and ibdal in the sentence. 2. The third interpretation of the commentators on polytheists in Q.S at-Taubah (9): 33 and Q.S as-Saf (61): 9 are those who have characteristics including: worshiping other than Allah Swt (Quraysh, Jews and Christians), having a dirty soul, and hating the emergence of Islam from the begining. Then in Q.S al-Fath (48): 28 which means